Clinical Observation of Patients with Leber's Hereditary Optic Neuropathy Before Gene Therapy - Yuan, Jiajia; Zhang, Yong; Liu, Hongli; Tian, Zhen; Li, Xin; Zheng, Yichen; Gao, Qin; Song, Lin; Xiao, Xiao; Sun, Jian; Wang, Zhitao; Li, Bin (Current Gene Therapy, 2018)
Background: Leber's hereditary optic neuropathy is a hereditary mitochondrial disease. No effective treatment has so far been established, with gene therapy currently being the most promising. Because of the possibility of spontaneous visual acuity recovery in this disease, we screened patients before gene therapy, excluding those with spontaneous visual acuity improvement, and prepared for the subsequent gene therapy. Objective: To clinically observe the course of Leber's hereditary optic neuropathy for 6 months prior to gene therapy. Methods: Sixty-six patients with Leber's hereditary optic neuropathy were enrolled in the study. Patients were classified based on the duration of disease: less than 24 months and over 24 months. Three clinical follow-up examinations were conducted over 1 year. We assessed intraocular pressure, visual acuity, visual field, retinal nerve fiber layer thickness, fundus photographs, and visual evoked potential. Results: Eighty-two eyes displayed stable visual acuity, including both eyes in 34 patients and one eye in 14 patients; 33 eyes of 22 patients displayed decrease in visual acuity (less than 24 months: 24 eyes; over 24 months: nine eyes); and 17 eyes of 12 patients showed improvement in visual acuity (less than 24 months: four eyes; over 24 months: 13 eyes). Visual acuity and visual field indices decreased over 24 months from disease onset and appeared stable after 24 months. Conclusion: Most patients with Leber's hereditary optic neuropathy gradually stabilize visual function with prolonged onset time, and the lower possibility of spontaneous vision recovery provides a basis for future evaluation of the effectiveness of gene therapy.
Keywords: visual evoked potential